Influence of Rohis Extracurricular Activities on Religious Character Enhancement (Activity Studies Rohis in SMAN 1 Kecamatan Siberut Utara) - Yudianto, Harbeni (Ruhama : Islamic Education Journal, 2024)
his article discusses the influence of Rohis extracurriculars on improving religious character (study of Rohis activities at SMAN 1 North Siberut District, Mentawai Islands Regency, West Sumatra Province).  Students are the main data source of quantitative research. Although the data collection method involves observation, questionnaires, and documentation, the data processing process consists of: validity test, reliability test, normality test, linearity test, and hypothesis testing results. The study results show that: rxy value - 0.0087. The level of correlation between variable students' religious character. Then, based on the proposed hypothesis, to determine the magnitude of the correlation coefficient using the t test formula, the t table value is obtained at a significance level of 5%, namely the calculated r which is greater than the r table, namely 0.541. Because the sig value is 0.200 = 0.05, H¹ is accepted, this means that the frequency distribution comes from a normally distributed population, which means that the hypothesis proposed in this research is accepted, which means there is an influence of Rohis extracurricular activities in improving religious character (Rohis activity study at SMAN 1 North Siberut District, Mentawai Islands Regency, West Sumatra Province).Keyword : Spiritual Extracurricular Activities, Religious Character